The shift to remote work lessens wage-growth pressures - Jose Maria Barrero; Nicholas Bloom; Steven J. Davis; Brent Meyer; Emil Mihaylov (Federal Reserve Bank of Atlanta, 2022)
The recent shift to remote work raised the amenity value of employment. As compensation adjusts to share the amenity-value gains with employers, wage-growth pressures moderate. We find empirical support for this mechanism in the wage-setting behavior of US employers, and we develop novel survey data to quantify its force. Our data imply a cumulative wage-growth moderation of 2.0 percentage points over two years. This moderation offsets more than half the real-wage catchup effect that Blanchard (2022) highlights in his analysis of near-term inflation pressures. The amenity-values gains associated with the recent rise of remote work also lower labor's share of national income by 1.1 percentage points. In addition, the "unexpected compression" of wages since early 2020 (Autor and Dube, 2022) is partly explained by the same amenity-value effect, which operates differentially across the earnings distribution.
Keywords: J3; E31; D22; E24; E25; 330; remote work; amenity value; wage growth; inflation dynamics; recession risk; business expectations; labor's share of national income; wage compression; Telearbeit; Lohnbildung; Lohnniveau; Lohnquote; USA